Indications of Brain Computed Tomography Scan in Children Younger Than 3 Years of Age with Minor Head Trauma - İsmail Gülşen; Hakan Ak; Sevdegül Karadaş; İsmail Demır; Mehmet Deniz Bulut; Soner Yaycioğlu (Emergency Medicine International)
Objective. To investigate the indications to receive brain computed tomography (CT) scan and to define the pathological findings in children younger than three years of age with minor head trauma in emergency departments. Methods. In this study, hospital case notes of 1350 children attending the emergency department of Bitlis State Hospital between January 2011 and June 2013 were retrospectively reviewed. 508 children under 3 years of age with minor head trauma were included in this study. We also asked 37 physicians about the indications for requiring CT in these children. Results. This study included 508 children, 233 (45,9%) of whom were female and 275 were male. In 476 (93,7%) children, the brain CT was completely normal. 89,2% of physicians asked in the emergency department during that time interval reported that they requested CT scan to protect themselves against malpractice litigation. Conclusion. In infants and children with minor head trauma, most CT scans were unnecessary and the fear of malpractice litigation of physicians was the most common reason for requesting a CT.